Preparation method of waterproof and fireproof high-performance coating
By sintering bamboo charcoal and bentonite into porous microspheres and embedded graphite inside them, combining the core-shell structure of composite microspheres and silica-starch sol, the existing fire-resistant coating is easily cracked and fallen, and high-performance waterproof and fire-resistant coatings are achieved.
Patent Information
- Application Number
- CN202411736639.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing solvent-free epoxy fire-repellent coatings are prone to cracking and falling off, especially under conditions of thick film thickness and large ambient temperature difference. Traditional waterproof coatings have problems such as low strength, poor durability and easy corrosion.
Bamboo charcoal and bentonite are used to sinter it into porous microspheres, and graphite is embedded inside it to form a heat-insulating-water barrier layer. By combining the core-shell structure of microspheres and silica-starch sols, the fire resistance of the coating is enhanced, and quaternary ammonium structure and hydrophobic alkyl end capping are introduced on the surface of the microspheres to improve antibacterial and waterproofing effects.
It effectively avoids breakdown or fall off of the organic carbon layer on the surface of the coating, improves fire resistance, and enhances the waterproof and antibacterial properties of the coating by forming a small carbon layer cavity and a hydrophobic alkyl structure.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a method for preparing a waterproof and fireproof high-performance coating. Background Art
[0002] At present, the intumescent fire retardant coatings used for hydrocarbon flames generally use epoxy resin as the film-forming material to ensure that the carbonized layer formed by the fire retardant coating after the fire retardant coating expands in the presence of hydrocarbon flames can withstand the impact of hydrocarbon flames without causing the carbonized layer to fall off or crack, thus avoiding the substrate from being exposed to flames too early and maintaining good fireproof properties. However, the common solvent-free epoxy fire retardant coatings currently have obvious defects: the fire retardant coating is prone to cracking and falling off, especially under conditions of thick film thickness and large ambient temperature difference.
[0003] In recent years, my country's building waterproof materials have developed rapidly, the market has continued to grow, and people's requirements for waterproof materials have also been increasing. Traditional waterproof coatings such as polyurethane, asphalt, epoxy resin, acrylic resin, etc., are applied to the surface of the base layer to form a waterproof membrane, but they all have problems such as low strength, poor durability, and susceptibility to corrosion. In addition, these coatings often require pre-treatment of the working surface before painting, and then adding a protective layer to achieve a more ideal effect. Summary of the invention
[0004] The purpose of the present invention is to provide a waterproof and fireproof high-performance coating and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a waterproof and fireproof high-performance coating, comprising the following preparation steps: (1) Bamboo charcoal and bentonite were mixed, ground at 60-150 rpm for 15 min, deionized water (0.1-0.3 times the mass of bamboo charcoal) was added, stirred at 100 rpm for 1-3 h, aged at room temperature for 24 h, granulated in a granulator to obtain spherical particles, dried at room temperature for 24 h, and sintered at 1180-1260 °C and normal pressure for 30-50 min in a nitrogen atmosphere to obtain porous microspheres; (2) Mix porous microspheres and graphite in a mass ratio of 10:1 and place them in a grinding device, with a ball-to-material ratio of 40:1 and grinding at 300 rpm for 30 min to obtain graphite-based microspheres; mix graphite-based microspheres, (chloromethyl)methyldiethoxysilane, ethanol, and deionized water, stir at 1000-2000 rpm for 15-30 min, filter, and dry to obtain modified porous microspheres; (3) The modified porous microspheres and dimethylaminoethyl acrylate were mixed, reacted at 55-60°C for 8-14 hours, petroleum ether was added, stirred at 100-200 rpm for 30 minutes, filtered, washed three times with ethanol and deionized water, and dried to obtain quaternized microspheres; (4) Mix trimethylol triglycidyl ether and quaternized microspheres and place them in an oil bath at 80-90°C, stir at 100 rpm for 1 hour, cool to 35°C, continue stirring for 1-1.5 hours, remove the oil bath, add maleic anhydride, concentrated sulfuric acid, and N,N-dimethylformamide, stir to dissolve, place in an oil bath at 70-75°C, continue stirring for 3 hours, add icy ether, let stand for 20-30 minutes, and filter to obtain composite microspheres; (5) 8-12 parts of composite microspheres and 14-30 parts of silica-starch sol were ground at a ball-to-material ratio of 20:1 at 300 rpm for 10-20 min, and 80-90 parts of epoxy resin E44, 10-20 parts of dodecyl glycidyl ether, 0.1-0.3 parts of defoamer BYK-093, 0.2-0.3 parts of wetting agent BYK-346, 0.3-0.4 parts of thickener RM-8W, 1-4 parts of dispersant BYK-220s, and 3-8 parts of 3,3,3-trifluoropropyltriethoxysilane were added. After stirring for 15-22 min, 6-10 parts of cardanol-type epoxy curing agent and 6-10 parts of ethylenediamine were added to obtain a waterproof and fireproof high-performance coating.
[0006] Furthermore, in step (1), the mass ratio of the bamboo charcoal to the bentonite is 20:10-44:25.
[0007] Furthermore, the particle size of the spherical particles in step (1) is 1-10 mm.
[0008] Furthermore, in step (2), the mass ratio of the graphite-based microspheres, (chloromethyl)methyldiethoxysilane, ethanol, and deionized water is 1:0.5-1.2:4-12:0.1-0.4.
[0009] Furthermore, in step (2), the drying temperature is 80° C. and the drying time is 12 h.
[0010] Furthermore, in step (3), the mass ratio of the modified porous microspheres, dimethylaminoethyl acrylate, and petroleum ether is 1:1-3:1-2.
[0011] Furthermore, in step (3), the drying temperature is 55° C. and the drying time is 12 h.
[0012] Furthermore, in step (4), the mass ratio of trimethylol triglycidyl ether, quaternized microspheres, maleic anhydride, concentrated sulfuric acid, N,N-dimethylformamide, and glacial ether is 2-4:1:4-6:0.05:3.5:0.5-1.2.
[0013] Furthermore, the preparation method of the silicon dioxide-starch sol in step (5) is as follows: starch and deionized water are mixed in a mass ratio of 2:10 to 5:20, stirred at 60°C and 400 rpm for 10 min, and then 1 to 3 times the mass of starch of ethyl orthosilicate and 8 to 12 times the mass of starch of anhydrous ethanol are added, and stirred at 15000 rpm for 3 to 6 min.
[0014] Furthermore, the stirring speed in step (5) is 800-1200 rpm.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention adopts composite microspheres and silica-starch sol composite grinding to coat the surface with silica-starch to form a core-shell structure. The shell structure can expand when encountering fire to form a hard inorganic foaming layer, which can effectively avoid the breakdown or shedding of the organic carbon layer on the surface of the core layer. At the same time, when the shell layer expands, the core layer forms a small carbon layer cavity, further improving the fire retardant performance of the coating.
[0016] The present invention utilizes bentonite and bamboo charcoal to mix and sinter into porous microspheres. While ensuring the porous structure of the bamboo charcoal itself, the bentonite is melted to form a liquid, which infiltrates the bamboo charcoal and makes the bamboo charcoal bonded together, so that the inside of the microsphere is loose and porous. The microsphere is ground and modified so that graphite is embedded in the porous inside. The bamboo charcoal can form a heat insulation and water-blocking layer to achieve the fireproof and waterproof performance of the coating. The addition of graphite can effectively block the conduction of temperature when encountering flames. Then, the silicon-oxygen bond of (chloromethyl)methyldiethoxysilane is grafted on the surface of the microsphere, and its chlorine group is bonded to the dimethylamino group of acrylic acid. The tertiary amine group of the ethyl ester reacts to form a quaternary ammonium structure, which makes the coating achieve an antibacterial effect, and then copolymerizes with trimethylol triglycidyl ether. Under the action of the catalyst, the epoxy group in trimethylol triglycidyl ether undergoes ring-opening polymerization, and at the same time, it can also catalyze the Michael addition reaction between the hydroxyl group in trimethylol triglycidyl ether and the double bond of dimethylaminoethyl acrylate, thereby forming a hydrophobic alkyl-terminated hyperbranched polymer on the surface of the microspheres, which can improve the waterproof effect of the fabric. At the same time, the hydrophobic alkyl group can be inserted into the bacterial cell membrane, ultimately leading to the death of the bacteria and improving the antibacterial properties of the coating. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the waterproof and fireproof high-performance coatings prepared in the following examples are as follows: Fire protection: The test sample is a 3 mm sandblasted steel plate, sprayed with 80 μm of the waterproof and fireproof high-performance coating of the embodiment and the comparative example, and the heating time of the heating curve is tested with reference to GA / T 714.
[0019] Antibacterial: Refer to HG / T 3950 to test the antibacterial rate.
[0020] Example 1 (1) Bamboo charcoal and bentonite were mixed in a mass ratio of 20:10, ground at 60 rpm for 15 min, and then 0.1 times the mass of bamboo charcoal was added with deionized water, stirred at 100 rpm for 1 h, aged at room temperature for 24 h, and granulated in a granulator to obtain spherical particles with a particle size of 1 mm. After drying at room temperature for 24 h, the particles were sintered at 1180 °C and normal pressure in a nitrogen atmosphere for 30 min to obtain porous microspheres. (2) Mix porous microspheres and graphite in a mass ratio of 10:1 and place them in a grinding device, with a ball-to-material ratio of 40:1 and grinding at 300 rpm for 30 min to obtain graphite-based microspheres; mix graphite-based microspheres, (chloromethyl)methyldiethoxysilane, ethanol, and deionized water in a mass ratio of 1:0.5:4:0.1, stir at 1000 rpm for 15 min, filter, and dry at 80°C for 12 h to obtain modified porous microspheres; (3) The modified porous microspheres and dimethylaminoethyl acrylate were mixed, reacted at 55° C. for 8 h, petroleum ether was added, stirred at 100 rpm for 30 min, filtered, washed with ethanol and deionized water three times in sequence, and dried at 55° C. for 12 h to obtain quaternized microspheres; the mass ratio of the modified porous microspheres, dimethylaminoethyl acrylate, and petroleum ether was 1:1:1; (4) Mix trimethylol triglycidyl ether and quaternized microspheres and place them in an 80°C oil bath, stir at 100 rpm for 1 hour, cool to 35°C, continue stirring for 1 hour, remove the oil bath, add maleic anhydride, concentrated sulfuric acid, and N,N-dimethylformamide, stir to dissolve, place in a 70°C oil bath, continue stirring for 3 hours, add glacial ether, let stand for 20 minutes, and filter to obtain composite microspheres; the mass ratio of trimethylol triglycidyl ether, quaternized microspheres, maleic anhydride, concentrated sulfuric acid, N,N-dimethylformamide, and glacial ether is 2:1:4:0.05:3.5:0.5; (5) Starch and deionized water were mixed in a mass ratio of 2:10, stirred at 60°C and 400 rpm for 10 min, and then 1 times the mass of starch and 8 times the mass of starch were added with tetraethyl orthosilicate and anhydrous ethanol, and stirred at 15000 rpm for 3 min to obtain silica-starch sol; 8 parts of composite microspheres and 14 parts of silica-starch sol were ground at a ball-to-material ratio of 20:1 and 300 rpm for 10 min, and then 80 parts of epoxy resin E44, 10 parts of dodecyl glycidyl ether, 0.1 parts of defoamer BYK-093, 0.2 parts of wetting agent BYK-346, 0.3 parts of thickener RM-8W, 1 part of dispersant BYK-220s, and 3 parts of 3,3,3-trifluoropropyl triethoxysilane were added, and stirred at 800 rpm for 15 min, and then 6 parts of cardanol-type epoxy curing agent and 6 parts of ethylenediamine were added to obtain a waterproof and fireproof high-performance coating.
[0021] Example 2 (1) Bamboo charcoal and bentonite were mixed in a mass ratio of 38:19, ground at 100 rpm for 15 min, and then 0.2 times the mass of bamboo charcoal was added with deionized water, stirred at 100 rpm for 2 h, aged at room temperature for 24 h, and granulated in a granulator to obtain spherical particles with a particle size of 6 mm. After drying at room temperature for 24 h, the particles were sintered at 1220 °C and normal pressure in a nitrogen atmosphere for 40 min to obtain porous microspheres. (2) Porous microspheres and graphite were mixed in a grinding device at a mass ratio of 10:1, with a ball-to-material ratio of 40:1 and ground at 300 rpm for 30 min to obtain graphite-based microspheres; graphite-based microspheres, (chloromethyl)methyldiethoxysilane, ethanol, and deionized water were mixed in a mass ratio of 1:0.9:8:0.3, stirred at 1500 rpm for 23 min, filtered, and dried at 80°C for 12 h to obtain modified porous microspheres; (3) The modified porous microspheres and dimethylaminoethyl acrylate were mixed, reacted at 58°C for 11 hours, petroleum ether was added, stirred at 150 rpm for 30 minutes, filtered, washed with ethanol and deionized water three times in sequence, and dried at 55°C for 12 hours to obtain quaternized microspheres; the mass ratio of the modified porous microspheres, dimethylaminoethyl acrylate, and petroleum ether was 1:2:1.5; (4) Mix trimethylol triglycidyl ether and quaternized microspheres and place them in an 85°C oil bath, stir at 100 rpm for 1 hour, cool to 35°C, continue stirring for 1.2 hours, remove the oil bath, add maleic anhydride, concentrated sulfuric acid, and N,N-dimethylformamide, stir to dissolve, place in a 72°C oil bath, continue stirring for 3 hours, add glacial ether, let stand for 25 minutes, and filter to obtain composite microspheres; the mass ratio of trimethylol triglycidyl ether, quaternized microspheres, maleic anhydride, concentrated sulfuric acid, N,N-dimethylformamide, and glacial ether is 3:1:5:0.05:3.5:0.9; (5) Starch and deionized water were mixed in a mass ratio of 3.5:15, stirred at 60°C and 400 rpm for 10 min, and then ethyl orthosilicate (2 times the mass of starch) and anhydrous ethanol (10 times the mass of starch) were added, and stirred at 15000 rpm for 5 min to obtain silica-starch sol; 10 parts of composite microspheres and 23 parts of silica-starch sol were ground at a ball-to-material ratio of 20:1 and 300 rpm for 15 min, and then 85 parts of epoxy resin E44, 15 parts of dodecyl glycidyl ether, 0.2 parts of defoamer BYK-093, 0.25 parts of wetting agent BYK-346, 0.35 parts of thickener RM-8W, 2 parts of dispersant BYK-220s, and 5 parts of 3,3,3-trifluoropropyl triethoxysilane were added, and stirred at 1000 rpm for 18 min, and then 8 parts of cardanol-type epoxy curing agent and 8 parts of ethylenediamine were added to obtain a waterproof and fireproof high-performance coating.
[0022] Example 3 (1) Bamboo charcoal and bentonite were mixed in a mass ratio of 44:25, ground at 150 rpm for 15 min, and then 0.3 times the mass of bamboo charcoal was added with deionized water, stirred at 100 rpm for 3 h, aged at room temperature for 24 h, and granulated in a granulator to obtain spherical particles with a particle size of 10 mm. After drying at room temperature for 24 h, the particles were sintered at 1260 °C and normal pressure in a nitrogen atmosphere for 50 min to obtain porous microspheres. (2) Mix porous microspheres and graphite in a mass ratio of 10:1 and place them in a grinding device, with a ball-to-material ratio of 40:1 and grinding at 300 rpm for 30 min to obtain graphite-based microspheres; mix graphite-based microspheres, (chloromethyl)methyldiethoxysilane, ethanol, and deionized water in a mass ratio of 1:1.2:12:0.4, stir at 2000 rpm for 30 min, filter, and dry at 80°C for 12 h to obtain modified porous microspheres; (3) The modified porous microspheres and dimethylaminoethyl acrylate were mixed, reacted at 60°C for 14 hours, petroleum ether was added, stirred at 200 rpm for 30 minutes, filtered, washed with ethanol and deionized water three times in sequence, and dried at 55°C for 12 hours to obtain quaternized microspheres; the mass ratio of the modified porous microspheres, dimethylaminoethyl acrylate, and petroleum ether was 1:3:2; (4) Mix trimethylol triglycidyl ether and quaternized microspheres and place them in a 90°C oil bath, stir at 100 rpm for 1 hour, cool to 35°C, continue stirring for 1.5 hours, remove the oil bath, add maleic anhydride, concentrated sulfuric acid, and N,N-dimethylformamide, stir to dissolve, place in a 75°C oil bath, continue stirring for 3 hours, add glacial ether, let stand for 30 minutes, and filter to obtain composite microspheres; the mass ratio of trimethylol triglycidyl ether, quaternized microspheres, maleic anhydride, concentrated sulfuric acid, N,N-dimethylformamide, and glacial ether is 4:1:6:0.05:3.5:1.2; (5) Starch and deionized water were mixed in a mass ratio of 5:20, stirred at 60°C and 400 rpm for 10 min, and then 3 times the mass of starch and 12 times the mass of starch were added with tetraethyl orthosilicate and anhydrous ethanol, and stirred at 15000 rpm for 6 min to obtain silica-starch sol; 12 parts of composite microspheres and 30 parts of silica-starch sol were ground at a ball-to-material ratio of 20:1 and 300 rpm for 20 min, and then 90 parts of epoxy resin E44, 20 parts of dodecyl glycidyl ether, 0.3 parts of defoamer BYK-093, 0.3 parts of wetting agent BYK-346, 0.4 parts of thickener RM-8W, 4 parts of dispersant BYK-220s, and 8 parts of 3,3,3-trifluoropropyl triethoxysilane were added, and stirred at 1200 rpm for 22 min, and then 10 parts of cardanol-type epoxy curing agent and 10 parts of ethylenediamine were added to obtain a waterproof and fireproof high-performance coating.
[0023] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (2) is changed to: bamboo charcoal and graphite are mixed in a mass ratio of 10:1 and placed in a grinding device, with a ball-to-material ratio of 40:1 and grinding at 300 rpm for 30 min to obtain graphite-based microspheres; graphite-based microspheres, (chloromethyl)methyldiethoxysilane, ethanol, and deionized water are mixed in a mass ratio of 1:0.9:8:0.3, stirred at 1500 rpm for 23 min, filtered, and dried at 80° C. for 12 h to obtain modified porous microspheres; the remaining steps are the same as those in Example 2.
[0024] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that there is no step (2). Step (2) is changed to: porous microspheres, (chloromethyl)methyldiethoxysilane, ethanol, and deionized water are mixed in a mass ratio of 1:0.9:8:0.3, stirred at 1500 rpm for 23 min, filtered, and dried at 80° C. for 12 h to obtain modified porous microspheres; the remaining steps are the same as in Example 2.
[0025] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that there is no step (3), and step (4) is changed to: trimethylol triglycidyl ether and modified porous microspheres are mixed and placed in an 85°C oil bath, stirred at 100 rpm for 1 hour, cooled to 35°C, and stirred for 1.2 hours, then the oil bath is removed, maleic anhydride, concentrated sulfuric acid, and N,N-dimethylformamide are added, stirred to dissolve, placed in an oil bath at 72°C, stirred for 3 hours, and then glacial ether is added. After standing for 25 minutes, the composite microspheres are filtered; the mass ratio of trimethylol triglycidyl ether, modified porous microspheres, maleic anhydride, concentrated sulfuric acid, N,N-dimethylformamide, and glacial ether is 3:1:5:0.05:3.5:0.9; the remaining steps are the same as those in Example 2.
[0026] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that step (4) is omitted, and step (5) is changed to: starch and deionized water are mixed in a mass ratio of 3.5:15, stirred at 60°C and 400 rpm for 10 min, and then ethyl orthosilicate twice the mass of starch and anhydrous ethanol 10 times the mass of starch are added, and stirred at 15000 rpm for 5 min to obtain silica-starch sol; 10 parts of quaternized microspheres and 23 parts of silica-starch sol are ground at a ball-to-material ratio of 20:1 and 300 rpm for 15 min. min, add 85 parts of epoxy resin E44, 15 parts of dodecyl glycidyl ether, 0.2 parts of defoamer BYK-093, 0.25 parts of wetting agent BYK-346, 0.35 parts of thickener RM-8W, 2 parts of dispersant BYK-220s, and 5 parts of 3,3,3-trifluoropropyltriethoxysilane, stir at 1000 rpm for 18 min, add 8 parts of cardanol type epoxy curing agent and 8 parts of ethylenediamine to obtain a waterproof and fireproof high-performance coating; the remaining steps are the same as those in Example 2.
[0027] Comparative Example 5 The difference between Comparative Example 5 and Example 2 lies in step (5). Step (5) is changed to: 10 parts of composite microspheres, 85 parts of epoxy resin E44, 15 parts of dodecyl glycidyl ether, 0.2 parts of defoamer BYK-093, 0.25 parts of wetting agent BYK-346, 0.35 parts of thickener RM-8W, 2 parts of dispersant BYK-220s, and 5 parts of 3,3,3-trifluoropropyltriethoxysilane are stirred at 1000 rpm for 18 min, and then 8 parts of cardanol type epoxy curing agent and 8 parts of ethylenediamine are added to obtain a waterproof and fireproof high-performance coating; the remaining steps are the same as those in Example 2.
[0028] Effect example Table 1 below shows the performance analysis results of the waterproof and fireproof high-performance coatings of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0029] Table 1 From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention mixes bentonite and bamboo charcoal to sinter into porous microspheres, and uses graphite to embed the pores of the microspheres, so as to form a heat insulation-water barrier layer in the coating. Then, (chloromethyl) methyl diethoxysilane, dimethylaminoethyl acrylate, and trihydroxymethyl triglycidyl ether are used for modification, and a quaternary ammonium structure is introduced on the surface of the microspheres to achieve the antibacterial property of the coating, and a hydrophobic alkyl-terminated hyperbranched polymer is formed on the surface of the microspheres, which can improve the waterproof effect of the fabric. At the same time, the hydrophobic alkyl can be inserted into the bacterial cell membrane, eventually leading to the death of the bacteria, thereby improving the antibacterial property of the coating. Then, silicon dioxide-starch is wrapped on the surface of the composite microspheres to form a core-shell structure. The shell structure can expand when exposed to fire to form a hard inorganic foaming layer, which can effectively avoid the breakdown or shedding of the organic carbon layer on the surface of the core layer. At the same time, when the shell layer expands, the core layer forms a fine carbon layer cavity, thereby further improving the fireproof performance of the coating.
[0030] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a waterproof and fireproof high-performance coating, characterized in that: The method comprises the following preparation steps: (1) Bamboo charcoal and bentonite were mixed in a mass ratio of 38:19, ground at 100 rpm for 15 min, and then 0.2 times the mass of bamboo charcoal was added with deionized water, stirred at 100 rpm for 2 h, aged at room temperature for 24 h, and granulated in a granulator to obtain spherical particles with a particle size of 6 mm. After drying at room temperature for 24 h, the particles were sintered at 1220 °C and normal pressure in a nitrogen atmosphere for 40 min to obtain porous microspheres. (2) Porous microspheres and graphite were mixed in a grinding device at a mass ratio of 10:1, with a ball-to-material ratio of 40:1 and ground at 300 rpm for 30 min to obtain graphite-based microspheres; graphite-based microspheres, (chloromethyl)methyldiethoxysilane, ethanol, and deionized water were mixed in a mass ratio of 1:0.9:8:0.3, stirred at 1500 rpm for 23 min, filtered, and dried at 80°C for 12 h to obtain modified porous microspheres; (3) The modified porous microspheres and dimethylaminoethyl acrylate were mixed, reacted at 58°C for 11 hours, petroleum ether was added, stirred at 150 rpm for 30 minutes, filtered, washed with ethanol and deionized water three times in sequence, and dried at 55°C for 12 hours to obtain quaternized microspheres; the mass ratio of the modified porous microspheres, dimethylaminoethyl acrylate, and petroleum ether was 1:2:1.5; (4) Mix trimethylol triglycidyl ether and quaternized microspheres and place them in an 85°C oil bath, stir at 100 rpm for 1 hour, cool to 35°C, continue stirring for 1.2 hours, remove the oil bath, add maleic anhydride, concentrated sulfuric acid, and N,N-dimethylformamide, stir to dissolve, place in a 72°C oil bath, continue stirring for 3 hours, add glacial ether, let stand for 25 minutes, and filter to obtain composite microspheres; the mass ratio of trimethylol triglycidyl ether, quaternized microspheres, maleic anhydride, concentrated sulfuric acid, N,N-dimethylformamide, and glacial ether is 3:1:5:0.05:3.5:0.9; (5) Starch and deionized water were mixed in a mass ratio of 3.5:15, stirred at 60°C and 400 rpm for 10 min, and then ethyl orthosilicate (2 times the mass of starch) and anhydrous ethanol (10 times the mass of starch) were added, and stirred at 15000 rpm for 5 min to obtain silica-starch sol; 10 parts of composite microspheres and 23 parts of silica-starch sol were ground at a ball-to-material ratio of 20:1 and 300 rpm for 15 min, and then 85 parts of epoxy resin E44, 15 parts of dodecyl glycidyl ether, 0.2 parts of defoamer BYK-093, 0.25 parts of wetting agent BYK-346, 0.35 parts of thickener RM-8W, 2 parts of dispersant BYK-220s, and 5 parts of 3,3,3-trifluoropropyl triethoxysilane were added, and stirred at 1000 rpm for 18 min, and then 8 parts of cardanol-type epoxy curing agent and 8 parts of ethylenediamine were added to obtain a waterproof and fireproof high-performance coating.
Citation Information
Patent Citations
Method for preparing bamboo charcoal with controllable aperture
CN104607145A
Constructional fireproof heat-insulation coating and preparation method thereof
CN108641527A
Method for preparing modified bamboo charcoal and application of modified bamboo charcoal
CN110240233A
Steel structure fireproof coating with excellent fireproof and heat-insulating properties, and preparation method thereof
CN111040522A
Method for preparing carbon microspheres with adjustable morphology and size by taking bamboo wood as raw material
CN117142455A